Enhanced internalization of nanoparticles following ionizing radiation leads to mitotic catastrophe in MG-63 human osteosarcoma cells - Popescu, Roxana Cristina; Straticiuc, Mihai; Mustăciosu, Cosmin; Temelie, Mihaela; Trușcă, Roxana; Vasile, Bogdan Ștefan; Boldeiu, Adina; Mirea, Dragoş; Andrei, Radu Florin; Cenușă, Constantin; Mogoantă, Laurenţiu; Mogoșanu, George Dan; et al. (International journal of molecular sciences, 2020)
This study aims to investigate whether ionizing radiation combined with doxorubicin-conjugated iron oxide nanoparticles (NP-DOX) improves the internalization and cytotoxic effects of the nano-carrier-mediated drug delivery in MG-63 human osteosarcoma cells. NP-DOX was designed and synthesized using the co-precipitation method. Highly stable and crystalline nanoparticles conjugated with DOX were internalized in MG-63 cells through macropinocytosis and located in the perinuclear area. Higher nanoparticles internalization in MG-63 cells previously exposed to 1 Gy X-rays was correlated with an early accumulation of cells in G2/M, starting at 12 h after treatment. After 48 h, the application of the combined treatment led to higher cytotoxic effects compared to the individual treatment, with a reduction in the metabolic capacity and unrepaired DNA breaks, whilst a low percent of arrested cells, contributing to the commitment of mitotic catastrophe. NP-DOX showed hemocompatibility and no systemic cytotoxicity, nor histopathological alteration of the main organs.